The natural course of bridging osteophyte formation on MRI-A pictorial illustration - Sirén Aapo; Mattila Kimmo; Hirvonen Jussi (United States, 2025)
Diffuse skeletal hyperostosis is a common spinal disorder, but its pathophysiology is mostly unclear. The disorder can lead to a variety of symptoms, but many patients remain relatively asymptomatic. We present a case demonstrating the development of bridging osteophytes on a series of magnetic resonance images. An elderly person's spine was scanned repeatedly due to non-specific back pain during the last 4 years and the consecutive images revealed the formation of a bony bridge in the lumbar spine. Extensive bone marrow edema was seen during the formation of the osteophyte, suggestive of an ongoing inflammatory process. This case underlines that the inflammatory reaction in diffuse skeletal hyperostosis can be intense and prolonged, and its role might be worth studying further.